2011
DOI: 10.1113/jphysiol.2011.217125
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised longitudinal MRI study of left ventricular adaptation to endurance and resistance exercise training in humans

Abstract: Non-technical summary This is the first study, to our knowledge, to use cardiac MRI before and after intensive and closely supervised resistance and endurance exercise training in humans. There is a long held belief that these different forms of training induce 'concentric' and 'eccentric' adaptation of the heart, but this concept is based on echocardiographic assessments and cross-sectional comparison of different types of elite athletes. Our findings, using highly sensitive MRI methodology, suggest that conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
168
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 23 publications
23
168
3
4
Order By: Relevance
“…This may explain the results of a recent longitudinal study in which individuals who maintained normal BP failed to develop LV hypertrophy during a 6-month period of strength training. 27 Our findings suggest that the concentric LV hypertrophy among strength athletes, traditionally presumed to be a benign adaptation, is actually a mild, previously unrecognized form of hypertensive LV remodeling that may carry adverse attendant prognostic implications. We therefore suggest that the term athlete's heart, typically used to imply a beneficial adaptive process, is not applicable to the concentric LV hypertrophy that develops among ASF linemen.…”
Section: Discussionmentioning
confidence: 94%
“…This may explain the results of a recent longitudinal study in which individuals who maintained normal BP failed to develop LV hypertrophy during a 6-month period of strength training. 27 Our findings suggest that the concentric LV hypertrophy among strength athletes, traditionally presumed to be a benign adaptation, is actually a mild, previously unrecognized form of hypertensive LV remodeling that may carry adverse attendant prognostic implications. We therefore suggest that the term athlete's heart, typically used to imply a beneficial adaptive process, is not applicable to the concentric LV hypertrophy that develops among ASF linemen.…”
Section: Discussionmentioning
confidence: 94%
“…Several longitudinal studies of EICR have recently been completed and have established with certainty, a mechanistic link between exercise exposure and sport/physiology-specific EICR. 11,20,21 To date, the few longitudinal studies that have been completed and published have involved relatively short duration exercise exposure and have focused on relatively young athletes. Work from the Harvard Athlete Initiative has shown that 90 days of intense team-based training is sufficient to produce the sport-specific forms of left ventricular remodeling described above.…”
Section: Myocardial Adaptations To Exercisementioning
confidence: 99%
“…With endurance exercise training there can be an increase in left ventricular mass and chamber volume without wall thickening, a phenomenon known as eccentric cardiac hypertrophy (326,447,483). This adaptation augments stroke volume and thus maximum cardiac output (maximum heart rate does not change much) (10,144,274,414).…”
Section: What Are the Effects Of Endurance Training?mentioning
confidence: 99%